2022
DOI: 10.1111/all.15272
|View full text |Cite
|
Sign up to set email alerts
|

T‐cell receptor sequencing specifies psoriasis as a systemic and atopic dermatitis as a skin‐focused, allergen‐driven disease

Abstract: Background Atopic dermatitis (AD) and psoriasis represent two of the most common inflammatory skin diseases in developed countries. A hallmark of both diseases is T‐cell infiltration into the skin. However, it is still not clarified to what extent these infiltrating T cells are antigen‐specific skin‐homing T cells or unspecific heterogeneous bystander cells. Methods To elucidate this, T cells from lesional skin and from blood of 9 AD and 10 psoriasis patients were compared by receptor (TCR) sequencing. Therefo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 63 publications
(110 reference statements)
5
17
0
Order By: Relevance
“…Interestingly it has recently been reported that an early-term effect of dupilumab treatment on IL-13, IL-4, IL-5 and IL-22 expression is preferentially found in circulating CD4 + CLA + T cells from AD patients ( 62 , 63 ). Besides this, circulating allergen-specific and CLA + T cells share the same TCRB CDR3 regions as lesional T cells from AD skin ( 64 ), supporting the relevance of our results for IL-31 produced by peripheral skin-homing T cells.…”
Section: Discussionsupporting
confidence: 84%
“…Interestingly it has recently been reported that an early-term effect of dupilumab treatment on IL-13, IL-4, IL-5 and IL-22 expression is preferentially found in circulating CD4 + CLA + T cells from AD patients ( 62 , 63 ). Besides this, circulating allergen-specific and CLA + T cells share the same TCRB CDR3 regions as lesional T cells from AD skin ( 64 ), supporting the relevance of our results for IL-31 produced by peripheral skin-homing T cells.…”
Section: Discussionsupporting
confidence: 84%
“…Propagated T-cell clones in AD and PS lesional skin have been reported to be detectable in clonalities of about 1%-10%. 19,53 In our set of data, we observed the highest levels of clonal expansion of T cells in the disease-specific cell clusters in lesional skin, indicating that these cells respond to disease-driving antigens. This effect was robust among the AD Th2/ Th22 as well as PS Th17/Tc17 cell clusters and implies that antigenrecognition is causative for the development of these clusters.…”
Section: Discussionmentioning
confidence: 63%
“…19 Furthermore, these bona fide disease-driving T cells are also detectable within circulating PBMC as so-called skin-homing T cells. 19 The sequencing approach applied here allows detection of clonally propagated T cells and phenotyping in parallel.…”
Section: Sctcr-seq Profiling Of Skin and Pbmcs Reveals Expanded And P...mentioning
confidence: 99%
“…The identification and characterization of allergen-specific T cells, their TCR sequences, and their reactive epitopes is critical for our ability to better treat patients with allergies (145). Studies on various tissue compartments and blood have broadly shown skewing of T cell repertoire usage with allergic disease (165)(166)(167)(168)(169). More targeted studies have examined the TCR repertoires and transcriptional profiles of antigen-specific T cells.…”
Section: Autoimmunity and Allergymentioning
confidence: 99%